PENGARUH PEMBERIAN BERBAGAI KADAR GETAH BUAH PEPAYA (Carica papaya, L.) TERHADAP JUMLAH KUMULATIF KEMATIAN LARVA Aedes aegypti - Widiastti, Rina; Ismiyati, Ismiyati; Aini, Resmi (Universitas Ahmad Dahlan, 2015)
AbstractBackground: Papaya is a kind of plats which has the medicinal effect. Papayaâs sap (latex) contains papain, cimopapain and lysozim as protein destructor enzyme. Satrija guess that these enzymes has an anthelmintical activity. The research aim was to know the influence of papayaâs sap (latex) as a larvacide in several kind of doses (concentration).Methods: This research was true experimental design with posttest only control group design. Papayaâs sap was made as powder, afterward it was used for the research to know influence of Papayaâs sap in several kinds of doses (consentration) related to larval cumulative mortality rate of Aedes aegypti. Larvicidal activity was calculated based on larval mortality after 24 hours of exposure that was taken notes for each treated group. Data processing used SPSS programÂ version 11,0 with significance 95% that contains data normality test, varians homogeneity test, One Way Anova, and Scheffe Post Hoc Test to know difference in larval cumulative mortality rate.Results: The result from Anova test shown a significant result in cause larval cumulative mortality rate of Aedes aegypti (p-value < 0.05) in comparison with negative gontrol group. Treated group with Papayaâs sap 1% shown higest larvacidal activity.Conclusion: Papayaâs sap has larvacidal activity at the concentration of 0,16%; 0,3%; 0,5%; and 1%. At concentration of 1%, papayaâs sap shown higest larvacidal activity and shown a significant result.Â Keywords: papaya, larvacide, larvae of Aedes aegypti